Other

# Ayudenn mañanaa. (-8)+(-14)-(-26)+(-18)b. (-39)-(-42)+(+81)-(+54)+(-114)c. (+106)-(+56)+(+78)-(+94)-(-36)d. (-68)-(-4)+(-73)-(+52)+(+106)e. (+78)-(+30)-(-37)+(+60)+(-45)-(-1)f. -12-14-16-18g. -18-20-22-24+20h. -2+6-10+6+10i. 18+21+24-6j. 4-6+10+6-16-18-2+9k. –(+12-13)+(-19-54)-(-11+15)-(+16)l. (-80)-(-14+67)+(-45+43)-(-32)-10m. –(-140+100-20)+(+65-45+13)-(-12)n. (-19+42-31+19)-(18+17-50)-(+36)o. 7+[-5+(+6-8)-(-4)]+[1+(6-3)]p. -3 – [2+ (5-7)+2+(-9+11)]q. – { -7 + [-3 – (-7+10-8)+10]-11}r. -9- [ -3-(1+2-3)+2]-[-3 – (2+5)]s. I -7I + I+12I – I18I – 4x9t. I -7-4I + I+11+10I – I-38 +10I – I-4I2

A.= (-14)

porque

(-8)+(-14)-(-26)+(-18)=

(-22)-(-26)+(-18)=

4+(-18)=

(-14)

B.=(-84)

porque

(-39)-(-42)+(+81)-(+54)+(-114)=

3+(+81)-(+54)+(-114)=

84-(+54)+(-114)=

30+(-114)=

(-84)

C.=70

porque

(+106)-(+56)+(+78)-(+94)-(-36)=

(+50)+(+78)-(+94)-(-36)=

(+128)-(+94)-(-36)=

(+34)-(-36)=

(+70)

D.=(-83)

porque

(-68)-(-4)+(-73)-(+52)+(+106)=

(-64)+(-73)-(+52)+(+106)=

(-137)-(+52)+(+106)=

(-189)+(+106)=

(-83)

E.=101

porque

(+78)-(+30)-(-37)+(+60)+(-45)-(-1)=

(+48)-(-37)+(+60)+(-45)-(-1)=

(+85)+(+60)+(-45)-(-1)=

(+145)+(-45)-(-1)=

(+100)-(-1)=

(+101)

F.=(-60)

porque

-12-14-16-18=

-26-16-18=

-42-18=

(-60)

G.=(-64)

porque

-18-20-22-24+20=

-38-22-24+20=

-60-24+20=

-84+20=

(-64)

H.=10

porque

-2+6-10+6+10=

4-10+6+10=

-6+6+10=

0+10=

10

I.=57

porque

18+21+24-6=

39+24-6=

63-6=

57

J.=(-13)

porque

4-6+10+6-16-18-2+9=

-2+10+6-16-18-2+9=

8+6-16-18-2+9=

14-16-18-2+9=

-2-18-2+9=

-20-2+9=

-22+9=

-13

K.=(-92)

porque

-(+12-13)+(-19-54)-(-11+15)-(+16)=

1-73-4-16=

-72-4-16=

-76-16=

-92

L.=(-113)

porque

(-80)-(-14+67)+(-45+43)-(-32)-10=

-80-53-2+32-10=

-133-2+32-10=

-135+32-10=

-103-10=

(-113)

M.=105

porque

-(-140+100-20)+(+65-45+13)-(-12)=

-60+33+12=

-27+12=

-15

N.=(-40)

porque

(-19+42-31+19)-(18+17-50)-(+36)=

11-15-36=

-4-36=

-40

O.=0

porque

7+[-5+(+6-8)-(+4)+[1+(6-3)]=

7+[-5+(-2)-4+[1+3]=

7+[-5+(-2)-4+4]=

7+(-7)=

0

P.=(-7)

porque

-3-[2+(5-7)+2+(-9+11)]=

-3-[2+(-2)+2+2]=

-3-4=

-7

Q.=6

porque

-{-7+[-3-(-7+10-8)+10]11}=

-{-7+[-3-(-5)+10]-11}=

-{-7+12-11}=

-(-6)=

6

R.=2

porque

-9-[-3-(1+2-3)+2]-[-3-(2+5)]=

-9-[-3-0+2]-[-3-7]=

-9-(-1)-(-10)=

2

mañana te envío el resto

6